2020
DOI: 10.1088/1755-1315/498/1/012105
|View full text |Cite
|
Sign up to set email alerts
|

Crane Accidents at Construction Sites in Malaysia

Abstract: Construction of high-rise buildings, large-scale apartment blocks, or construction in urban areas demands increasingly greater use of cranes. In the construction industry, the use of crane is common and very important regardless of the size of the project. Cranes generally use cable and pulley to deliver a mechanical advantage when it is necessary to lift heavy loads. They have the potential to move materials of different sizes that play an extraordinarily important role in the construction site. The crane ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Additionally, it was also stated that the impact of low and limited budget allocation on safety and health practices has resulted in a lack of enforcement, monitoring, and safety audits of mandatory safety and health regulations. The aforementioned factors, which have also been seen in a number of studies, have been shown to have the same effect of contributing to poor site management in terms of occupational safety and health practices (Hashim et al 2016;Muhamad Zaini et al 2020;Rajendran, 2020). These findings bolster evidence of the construction sector and its associated building sites have a poor track record in safety management.…”
Section: Occupational Safety and Health Act 1994mentioning
confidence: 85%
See 2 more Smart Citations
“…Additionally, it was also stated that the impact of low and limited budget allocation on safety and health practices has resulted in a lack of enforcement, monitoring, and safety audits of mandatory safety and health regulations. The aforementioned factors, which have also been seen in a number of studies, have been shown to have the same effect of contributing to poor site management in terms of occupational safety and health practices (Hashim et al 2016;Muhamad Zaini et al 2020;Rajendran, 2020). These findings bolster evidence of the construction sector and its associated building sites have a poor track record in safety management.…”
Section: Occupational Safety and Health Act 1994mentioning
confidence: 85%
“…Statistics from the Department of Workplace Safety and Health (DOSH) Malaysia indicate that the construction industry poses the highest risk of occupational accidents and fatalities (Affandi & Chia, 2013). This is supported by annual reports of over 200 impairments and deaths (Muhamad Zaini et al 2020). This is reinforced by research indicating that the high figures are a result of the current methods of safety and health management in the construction industry, which are deemed to be inadequate in terms of commitment from middle and top management, an inadequate workforce, and budget allocations (Affandi & Chia, 2013).…”
Section: Occupational Safety and Health Act 1994mentioning
confidence: 95%
See 1 more Smart Citation
“…Hamid et al [ 14 ] asserted that there was 125% increase of fatal injuries on construction sites in Malaysia from 2009 to 2015. Similarly, according to Muhamad Zaini et al [ 13 ], fatalities on construction sites experienced an approximately 30% rise over a four-year period, starting from the year 2015. In contrast to developing counties, the status quo in developed countries is significantly better.…”
Section: Introductionmentioning
confidence: 93%
“…Another developing country, whose construction industry constitutes a major proportion of fatal- and non-fatal accidents recorded among all industries, is Malaysia. Though the construction industry has recently evolved, thanks to the use of modern technology and equipment, yet the rate of accidents on construction sites has not noticeably decreased [ 13 ]. Hamid et al [ 14 ] asserted that there was 125% increase of fatal injuries on construction sites in Malaysia from 2009 to 2015.…”
Section: Introductionmentioning
confidence: 99%